Structural modeling and evolution of the piedmont zone in north margin of Qaidam Basin, northeastern Tibetan Plateau. Issue 6 (November 2020) - Zongxing, Li; Dahua, Wang; Xianchao, Wang; Yongjun, Xiao; Bo, Peng
The analysis and interpretation of the Dachaidan area, Qaidam Basin, is difficult, owing to the co-location of two groups of thrust faults (N–E faults and N–W faults) there and the area's complicated structural deformation history. To address this problem, field geological investigation, seismic study, well logging, and drilling data were used to identify the key fault systems and their distribution patterns through the area. By integrating surface and subsurface structural features and seismic and non-seismic data, we carried out studies using structural modeling and analysis of the Dachaidan area. Study results identified two systems of thrust faults (N–W faults and W–E faults). We found that these faults could be categorized into three systems: a basin-margin thrust system, an intro-basin thrust system, and an intro-basin compression and strike-slip fault system. These systems showed different features in different areas and zones. We also constructed interpretation models of different deformation mechanisms in the basin and on basin margins. Three tectonic systems (compression, extension, and strike-slip) were identified, which were further divided into eight structural domains. We also established structure coexistence and distribution patterns. The overall structural character of the area was summarized as the northern and southern parts belonging to different zones, with the western and eastern parts belonging to different systems. By analyzing the SW–NE tectonic evolution sections, we defined the back-propagation structural evolution sequences of thrust nappes (on the basin margin or in the basin) and back-thrust structures (in the basin) as well as their influence on the residual Mesozoic strata.